A Political Ecology of Youth and Crime - France, A. author. aut Link
VIII, 203 p.
Keywords: This book explores young people's 'nested' and 'political' ecological relationships with crime through an empirical investigation of the important 'places' and 'spaces' in young people's lives; in their social relationships with peers and family members; and within formal institutional systems such as education, youth justice and social care.